First results from the JWST early release science program Q3D: turbulent times in the life of a z ∼ 3 extremely red Quasar revealed by NIRSpec IFU - Wylezalek, Dominika; Vayner, Andrey; Rupke, David S. N.; Zakamska, Nadia L.; Veilleux, Sylvain; Ishikawa, Yuzo; Bertemes, Caroline; Liu, Weizhe; Barrera-Ballesteros, Jorge K.; Chen, Hsiao-Wen; Goulding, Andy D.; Greene, Jenny E.; et al. (The astrophysical journal. Part 2, Letters, 2022)
Extremely red quasars, with bolometric luminosities exceeding 1047 erg s−1, are a fascinating high-redshift population that is absent in the local universe. They are the best candidates for supermassive black holes accreting at rates at or above the Eddington limit, and they are associated with the most rapid and powerful outflows of ionized gas known to date. They are also hosted by massive galaxies. Here we present the first integral field unit observations of a high-redshift quasar obtained by the Near Infrared Spectrograph on board the James Webb Space Telescope (JWST), which targeted SDSS J165202.64+172852.3, an extremely red quasar at z = 2.94. The JWST observations reveal extended ionized gas—as traced by [O iii] λ5007 Å—in the host galaxy of the quasar, its outflow, and the circumgalactic medium. The complex morphology and kinematics imply that the quasar resides in a very dense environment with several interacting companion galaxies within projected distances of 10-15 kpc. The high density of the environment and the large velocities of the companion galaxies suggest that this system may represent the core of a forming cluster of galaxies. The system is a good candidate for a merger of two or more dark matter halos, each with a mass of a few 1013 M ⊙, and potentially traces one of the densest knots at z ∼ 3.
Gesehen am 03.01.2023